Explorations An Open Invitation To Biological Anthropology - Shook, Beth; Nelson, Katie; Aguilera, Kelsie (Open textbook library., 2019)
Anthropology is the study of humanity, in all its biological and cultural aspects, past and present. It is a four-field discipline comprised of biological anthropology, cultural anthropology, archaeology, and linguistic anthropology. The focus of this book is biological anthropology, which explores who we are from biological, evolutionary, and adaptive perspectives. We lay the foundation for this inquiry in the first four chapters by introducing the discipline of anthropology, evolutionary theory, molecular biology and genetics, and the forces of evolution. Chapters 5–8 consider evolutionary, biological, and social aspects of our closest living relatives, nonhuman primates, with whom we share millions of years of evolution. We also learn about how fossils provide material insight into our past. Chapters 9–12 describe prior hominin species and the emergence of Homo sapiens, us! Finally, the last four chapters (Chapters 13–16) explore human biological variation and the concept of race, bioarchaeology and forensic anthropology, and human biology and health in the past and present. We include further readings on osteology (Appendix A), primate conservation (Appendix B), and human behavioral ecology (Appendix C). To guide your reading, each chapter begins with learning objectives and ends with review questions and a list of key terms. Ancillary materials are available for this textbook.